Irrigação por sulcos para o cultivo de milho em áreas de arroz irrigado - Chaiben Neto, Miguel (2019)
The use of rainfed crops in rotation with iwith irrigated rice in the lowland areas of the state of Rio Grande do Sul, has shown as an alternative to reduction weed infestation in rice growing areas. However, the environment naturally found in these areas is not conducive to the cultivation of rainfed crops. The use of corn in these rotations has benefits in the control of weeds and reduction in the soil seed bank. However, their cultivation in these areas is subject to the naturally occurring edaphoclimatic limitations, stress due to excess or water deficit can significantly limit grain yield of the crop. The utilization of cultivation techniques that reduce these stresses is fundamental to the success of the productive system. Corn cultivation in grooves shows up to possible alternative because of the groove formed between the ridges, which helps the drainage and facilitates irrigation management. Studies that relate maize cultivation in floodplain areas with irrigation by grooves may contribute to the proper introduction of this crop in rotation with rice in these areas. In view of the above, the present work has the objective of evaluating the performance of irrigation by furrows under different management of water replenishment time in the parameters of irrigation system sizing and efficiency, water use efficiency, growth and grain yield corn in the lowlands. The experiment was conducted in a two - factorial arrangement, were evaluated the effect of 5 irrigation treatments and 3 positions along the experimental unit. During the crop cycle, was evaluated corn growth and yield parameters and irrigation parameters. During the vegetative period of the crop, the irrigations had no presented effect in the growth components of the same. In the reproductive period, there was response to irrigation, increasing the productivity grain yield from 43.81 until 53.26% for treatments with 100 and 0% of the time required for the replacement of irrigation slides, the application efficiency was upper for the treatments with zero and 25% of replacement, being 89.46 and 81.66%, respectively. Irrigation management did not influence the components in maize growth and yield at the three evaluated positions, the water use efficiency and efficiency irrigation water did not present differences for the treatments tested.